Online news report headlines of Education Malaysia Global Services - Yuen, Chee Keong; Sidra Naim; Noor Darliza Mohamad Zamri (Universiti Kebangsaan Malaysian, 2014)
This research aims to reveal the representations of the Education Malaysia Global Services (EMGS) policy change on the new visa application procedure announced in 2013 and to unravel the ways in which ideology and context shape the discourse surrounding EMGS through an analysis of news report headlines. Using Critical Discourse Analysis on the themes and lexical choices of headlines from the period of February 2013 to April 2014, the general characteristics of the news reports headlines disclose that there are ideological differences at play and these ideologies are reflected differently according to the sources of the headlines. In Malaysian media, the reporting on EMGS has been framed according to the political stance of newspapers: in a positive supportive way by the government linked media; The NST, BERNAMA and The Star, and in a negative way in the alternative, or non-government linked media; Malaysiakini and Borneo Post. In the global media (UK, US, Singapore, Brunei) newspapers (The Straits Times, Investor News, Asia One, The Sunday Times) also highlight a negative view on the policy change. These reporting styles show differences in situational context and ideology that shaped the discourse of the headlines, contributing significantly to the portrayal of EMGS, especially to potential students from all around the world in particular ways.